1998
DOI: 10.1063/1.368352
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and structural properties of poly-Si films grown by furnace and rapid thermal annealing of amorphous Si

Abstract: In the present work, the effect of rapid thermal annealing (RTA) on the electrical and structural properties of poly-Si thin films, grown by the crystallization of a-Si films deposited by rapid thermal low-pressure chemical vapor deposition, has been studied. Structural and electrical results were obtained using atomic force microscopy, transmission electron microscopy, electron spin resonance, electrical resistivity, and Hall mobility techniques. The effects of the grain size, grain boundaries, and surface ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…As it was reported, trap densities can be reduced by increasing the temperature and time of the thermal annealing due to the extinction of crystal defects [10]. Additionally, it was found that RTA treatment of the SPC poly-Si films can decrease the electron spin density from 2.3 Â 10 17 cm À 3 to 2.9 À3.2 Â 10 16 cm À 3 [11]. In poly-Si, the electron spin resonance signal arises mainly from Si dangling bonds from grain boundaries [12].…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…As it was reported, trap densities can be reduced by increasing the temperature and time of the thermal annealing due to the extinction of crystal defects [10]. Additionally, it was found that RTA treatment of the SPC poly-Si films can decrease the electron spin density from 2.3 Â 10 17 cm À 3 to 2.9 À3.2 Â 10 16 cm À 3 [11]. In poly-Si, the electron spin resonance signal arises mainly from Si dangling bonds from grain boundaries [12].…”
Section: Resultsmentioning
confidence: 91%
“…In poly-Si, the electron spin resonance signal arises mainly from Si dangling bonds from grain boundaries [12]. Thus, RTA treatment can decrease the dangling bonds density at the grain boundaries in SPC poly-Si [11]. Based on the reasons above, RTA treatment can improve the electronic properties of the SPC seed layer.…”
Section: Resultsmentioning
confidence: 95%
“…The electron spin resonance technique has been used to measure the spin density, which is correlated to the density of dangling bonds at grain boundaries, and defects within the grain. It has been shown that high temperature RTA reduces the spin density and (or) dangling bond density (compared to infrared furnace) resulting in poly-Si films of good electrical quality (as confirmed by Hall mobility measurements) [11]. Thus, RTA has the capability of greatly improving c-Si film characteristics by reducing the density of dangling bonds and in-grain microtwins.…”
Section: Electrical Characterization Of Fabricated Solar Cells Using Rtamentioning
confidence: 93%
“…Microtwins may terminate inside a grain and act as scattering centres. Microtwin defects are unstable, and it has been shown that their density can be drastically reduced with RTA annealing temperatures above 750°C [11]. The electron spin resonance technique has been used to measure the spin density, which is correlated to the density of dangling bonds at grain boundaries, and defects within the grain.…”
Section: Electrical Characterization Of Fabricated Solar Cells Using Rtamentioning
confidence: 99%
“…Poly-Si TFTs are generally made by depositing a-Si:H thinfilm onto a glass sheet using chemical vapor deposition (CVD) and subsequently exposing the deposited glass to high temperatures for a sufficient period of time to crystallized the a-Si:H into poly-Si, which has been named "solid-phase crystallized (SPC) poly-Si" [13], [14]. This crystallization step is typically performed at 600 • C for several tens of hours, or alternatively, rapid thermal annealing [15] or laser excimer annealing [16] can be employed, wherein a laser or, some other source of a sharp temperature gradient, can be used to minimize the heating of the glass substrate [17]. In either case, however, the substrate still experiences a temperature of 400 to 600 • C.…”
Section: Introductionmentioning
confidence: 99%